Analysis of Land Plot Sales Using the C4.5 Algorithm in Property and Housing Sector - Syahrin, Rizky Alfi (Informatics and Software Engineering, 2024)
This research examines the application of the C4.5 algorithm in analyzing land plot sales data at PT Piliruma Rosa Land. Using data from two main projects, namely Harmoni Farm House and Nuansa Alam Agroewisata and Luxury, this study aims to build a decision tree model that is effective in predicting consumer interest. The analysis was conducted by evaluating the contribution of various sales attributes, specifically Sold Area and Number of Sold Lots, which proved to have a significant impact on the classification of buyer interest. The results of the model showed an accuracy rate of 91.18%, signifying the effectiveness of the C4.5 algorithm in assisting strategic decision-making in the property sector. The findings provide important insights for real estate developers in optimizing marketing and sales strategies, while offering a reliable analytical method for similar sectors.   Penelitian ini mengkaji penerapan algoritma C4.5 dalam menganalisis data penjualan tanah kavling pada PT Piliruma Rosa Land. Melalui data dari dua proyek utama, yaitu Harmoni Farm House dan Nuansa Alam Agroewisata dan Luxury, penelitian ini bertujuan untuk membangun model pohon keputusan yang efektif dalam memprediksi minat konsumen. Analisis dilakukan dengan mengevaluasi kontribusi dari berbagai atribut penjualan, khususnya luas terjual dan jumlah kavling terjual, yang terbukti memberikan dampak signifikan terhadap klasifikasi minat pembeli. Hasil dari model ini menunjukkan tingkat akurasi sebesar 91.18%, menandakan efektivitas algoritma C4.5 dalam membantu pengambilan keputusan strategis di sektor properti. Temuan ini memberikan wawasan penting bagi pengembang real estat dalam mengoptimalkan strategi pemasaran dan penjualan, sekaligus menawarkan metode analitis yang bisa diandalkan untuk sektor serupa.